Perkembangan Histologis Ovarium Bayi dan Anak Owa Jawa (Hylobates moloch) (HISTOLOGICAL DEVELOPMENT OF NEONATE AND JUVENILE JAVAN GIBBON (Hylobates moloch) OVARIES) - Notosoediro, Pristiani Nurantika; Winarto, Adi; Tumbelaka, Ligaya Innocentia Theresia Antoinetta (Jurnal Veteriner, 2019)
Reproductive success is one of the biggest challenges for the existence of javan gibbon (Hylobates moloch) in the future. Basic biology information of main reproduction female organ of the species is yet unknown. The research aimed to provide information of female ovary development through histological examination. Two pairs of ovaries were collected from a neonate and a three years old female cadaver at Javan Gibbon Center. Histological techniques (cross and longitudinal sections) were applied to the collected samples using paraffin method with haematoxylin eosin (HE) and Masson’s trichrome (MT) dyes. The follicles are spread evenly in the left and right cortex ovary. The number of primordial follicles within the neonate and infant ovary was 80 815 and 34 622, respectively. In a three years old javan gibbon ovaries, the development of primordial into primary, pre-antral and antral follicles were observed. The average diameter of the follicles and oocytes were, respectively; 25.0±8.9 ?m and 20.0±13.1 ?m for primordial follicle, 48.4±22.5 ?m and 20.5±10.0 ?m for primary follicle, 79.0±49.0 ?m and 25.4±17.4 ?m for pre-antral follicle, 315.5±36.1 ?m and 32.0±17.0 ?m for antral follicle. The size of primordial and primary oocyte and follicle of javan gibbon is smaller than those of Macaca fascicularis at the same age. The connective tissue of neonate ovary was being developed while in the 3 years old female ovary, it was well-developed and clearly seen in the capsula, cortex, and medulla. Javan gibbon follicle development is strongly influenced by age.